Inflammatory Pseudotumor of the Temporal Bone Leading to Atypical Superior Semicircular Canal Dehiscence Syndrome: A Novel Case Report. Issue 8 (September 2021) - Smith, Blaine D.; Cunningham, Calhoun D.
Abstract : Objective: Inflammatory pseudotumor of the temporal bone is a benign idiopathic inflammatory process that is rarely encountered in clinical practice. We describe a novel case of a patient who developed superior semicircular canal dehiscence syndrome in the setting of active inflammatory pseudotumor of the temporal bone. Patient: One female patient found to have inflammatory pseudotumor of the temporal bone. After treatment with mastoidectomy and steroids, she subsequently developed superior semicircular canal dehiscence syndrome. Intervention(s): The patient initially underwent myringotomy and pressure equalization tube placement for a unilateral effusion. Imaging with computed tomography and magnetic resonance imaging revealed a lytic mastoid mass. A complete mastoidectomy was diagnostic for inflammatory pseudotumor and the patient was treated with adjuvant long-term corticosteroids. After this procedure, she was discovered to have new development of symptomatic superior semicircular canal dehiscence syndrome. She eventually underwent a trans-mastoid repair of her superior semicircular canal dehiscence. Main Outcome Measure(s): The patient's clinical course is described with emphasis on the development of superior semicircular canal dehiscence syndrome in the setting of active inflammatory pseudotumor of the temporal bone. Results: The patient's radiographic and clinical history were found to be consistent with inflammatory pseudotumor of the temporal bone. She underwent a therapeutic mastoidectomy with long-term post-operative corticosteroids. During her post-operative course, she developed symptoms of vertigo, hearing loss, and autophony. She was subsequently diagnosed with superior semicircular canal dehiscence and treated with a trans-mastoid repair of the dehiscence. Her symptoms satisfactorily resolved after this surgery. Conclusions: Inflammatory pseudotumor of the temporal bone is a rare benign inflammatory process. We present what is to our knowledge the first description of superior semicircular canal dehiscence syndrome developing in the setting of inflammatory pseudotumor.